GAMBARAN FAKTOR PREDISPOSISI BIOLOGI PADA KLIEN GANGGAUN JIWA DI RSJD Dr. AMINO GONDHOHUTOMO SEMARANG - Nanang Khosim Azhari; Tuti Anggarawati; Kandar (SEKOLAH TINGGI ILMU KESEHATAN KESDAM IV DIPONEGORO, 2023)
Background: Mental health is a picture of positive characteristics with harmony and psychological balance that reflects the maturity of his personality. Meanwhile, mental disorders are behavioral patterns that clinically occur in individuals related to distress or disability or are accompanied by a significantly increased risk of death, illness, disability, or loss of independence. According to WHO (World Health Organization) the prevalence of mental disorders in the world is around 450 million people. The high rate of recurrence in people with mental disorders requires us to be more active in knowing the causes. The purpose of this study is to find out an in-depth description of the biological causal factors of a person experiencing mental disorders. This research method uses descriptive qualitative research. Samples were taken randomly with the criteria of someone with a Mental Disorder (ODGJ). The population of this study were mental patients who were treated at RSJD Dr. Amino Gondhohutomo Semarang. The research instrument used a mental disorder predisposition questionnaire. The questionnaire has construct validity and reliability and has been used during Residencies I to III. The results of this study showed that of the 106 respondents who had biological predisposing factors, a history of mental disorders was 39%, followed by a history of drug withdrawal of 38.1%, and the lowest was nutritional disorders.